ANALYSIS OF BATHYMETRIC DATA UTILIZATION FOR UNDERWATER MORPHOLOGY VISUALIZATION IN JEMAJA ANAMBAS ISLANDS RIAU ISLANDS INDONESIA - Bayu Dwi Santoso; Puspita Indra Wardhani; Ratih Puspita Dewi; Fitra Annurhutami (GeoEco, 2024)
Administratively, Pulau Jemaja is located in the Kepulauan Anambas Regency, Riau Islands Province, which lies between 2°10'0" - 3°40'0" N and 105°15'0" - 106°45'0" E. This area is situated on the outermost border of the Unitary State of the Republic of Indonesia and possesses potential natural resources. The potential resources available in the Natuna Regency, especially on Pulau Jemaja, include coral reefs, mangroves, marine sediment/sand, petroleum, and fishery resources. The presence of these resources on Pulau Jemaja, coupled with its location on the national border, is crucial in determining the research location. This study utilizes two sets of secondary data: bathymetric data issued by Pushidrosal of the Indonesian Navy and BATNAS (National Bathymetric Mapping) data issued by BIG (Geospatial Information Agency). The aim of this research is to determine the morphology of the seabed in the Jemaja port area by comparing the bathymetric data from Pushidrosal and BATNAS (BIG) with a resolution of 6 arc-seconds. The method used in this research is GIS with the assistance of ArcGIS and Surfer software. Data analysis in this study employs descriptive analysis, utilizing comparison tables. Prior to analysis, data preprocessing was conducted to facilitate analysis. The results of this study indicate that the maximum depth in this area is -36 meters according to the data issued by Pushidrosal, while the data from BIG indicates a maximum depth of -40 meters. The seabed morphology around the waters of Jemaja falls within the Continental Shelf. The 3D modeling results show differences due to the varying spatial resolution between the two datasets.